Modeling collaborative practical work processes in an E-learning context of engineering electric education - Fahd Ouatik; Mustapha Raoufi; Mohamed El Mohadab; Farouk Ouatik; Belaid Bouikhalene; Mohammed Skouri (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This work deals with the modeling  the processes of the collaboration in practical work of electronics in a context of e-learning and the remote laboratory which is a new technology allows students to manipulate the practical experience the electronics by controlling all equipments  and instruments of a laboratory via the web without moving to t laboratory. That is for to solve the problems of overcrowding students in universities and the restriction of  time and places and the lack of some instrument in laboratory.  Even this new project will allow the sharing all  instruments and equipments between  universities in the world for to have a cooperation in scientific learning. In this work we are interested to modeling the processes of collaborative electronics practical work, whose actors are :   tutor,  member,  coordinator and the secretary and collaborative tools. Two models have been developed: a tutor-student model showing the activities of the learner and  tutor, and  moderating-member-secretary model that focuses more specifically on the roles of the moderator (coordinator) and the secretary (reporter). This modelling has made it possible to better understand the processes considered and to detect the various problems that may arise during an online particle work collaborative process.